Navigating The Flow of Challenges: Problematics of Implementing Kurikulum Merdeka in Sociological Subject at SMAN 1 Tumpang - Malang - Alya Muflihatud Dini; Alan Sigit Fibrianto; Ahmad Tirtho Faidl Huda; Annisa Shafa Azzahra; Lutfia Cempaka; Nabila Nasywal Muna; Nia Lestari; Titis titis (JSPH (Jurnal Sosiologi Pendidikan Humanis), 2023)
The Merdeka Curriculum aims to empower students with a more independent and innovative learning approach. However, the process of implementing the Independent Curriculum in sociology learning at SMAN 1 Tumpang was faced with several problems. This article aims to identify and analyze the challenges, difficulties, solutions, and strategies for implementing the Merdeka curriculum in the context of learning sociology at SMAN 1 Tumpang. The method used is descriptive qualitative research with data collection techniques through observation, interviews, and documentation. The research subjects were selected using a purposive sampling technique, namely one of the Sociology teachers at SMAN 1 Tumpang who was involved in the learning process and school staff related to implementing the independent curriculum. The study results show that implementing the independent curriculum at SMAN 1 Tumpang brings several challenges that require the active role of educators in identifying the needs and abilities of individual students. Making teaching modules, teacher difficulties in implementing P5, and learning administration. In dealing with these difficulties, the Sociology teacher at SMAN 1 Tumpang took various strategic solutions, such as integrating technology in education, providing training and coaching to teachers, and creating collaboration between teachers and students.